Human T-cell recognition of Listeria monocytogenes: recognition of listeriolysin O by TcR alpha beta + and TcR gamma delta + T cells. - Guo, Y (1995)
The cell-mediated immune response to Listeria monocytogenes has been well characterized in the mouse. Listeriolysin O (LLO) is a major antigen in murine T-cell recognition of L. monocytogenes. In this study, we show that LLO is also recognized by human TcR alpha beta T cells and TcR gamma delta T cells. Human peripheral blood mononuclear cells (PBMC) cultured in vitro with live listeriae and then expanded with interleukin 2 were shown to respond to purified LLO. The generation of LLO-responsive T cells was dependent on the use of live bacteria during the initial in vitro challenge. LLO-induced proliferation of T cells expanded by exposure of PBMC to live listeriae was major histocompatibility complex restricted. PBMC cultured with formalin-fixed listeriae and subsequently expanded by interleukin 2 gave high proliferative responses to fixed bacteria but failed to respond to LLO. PBMC stimulated in vitro with fixed listeriae contained predominantly TcR alpha beta + T cells. In contrast, PBMC obtained from 85% of the donors studied generated high numbers of TcR gamma delta + T cells following in vitro culture with live listeriae. Using a panel of synthetic amphipathic LLO peptides, we found that LLO-specific T cells from different individuals recognized both common and unique peptides. LLO 470-508 was recognized by three of five individuals, while LLO 203-226 and LLO 107-126 were recognized by two of six individuals. A TcR gamma delta + T-cell line was established from PBMC stimulated with live listeriae and was shown to recognize LLO 470-508. Proliferative responses could be induced in this cell line by peptide-pulsed autologous PBMC but not by peptide-pulsed allogeneic PBMC. Our results establish the importance of LLO in human T-cell recognition of listeriae and show that both TcR alpha beta + T cells and TcR gamma delta + T cells recognize this antigen. Finally, since LLO 470-508 has a high degree of homology with other gram-positive bacterial toxins, the recognition of this peptide by TcR gamma delta + T cells suggests that an important role of these T cells in host defense is the recognition of bacterium-derived toxins.